Risk Factors for Diabetes Mellitus: a Comparative Analysis of Subpopulation Differences in a Large Canadian Sample - Taylor, Michael James (Scholarship@Western, 2013)
Objectives: Certain Canadian subpopulations observe numerous modifiable and non-modifiable risk factors for diabetes. This study compares immigrants and Aboriginals (First Nations, Inuit, and Métis) with Canada-born individuals at higher risks for diabetes, and deciphers the determinant differences between them. Methods: Pooled Canadian Community Health Survey data (2001-2010) were used. Time trends for diabetes within each subsample were calculated using individual survey year prevalence rates; diabetes diagnoses were self-reported (N=33,565). Various risk factors were also examined using logistic regression. Results: Diabetes prevalence rates significantly increased from 2001 to 2010 for each subpopulation, as well as the total sample: Canada-Born individuals (3.9% to 5.7%), Immigrants (5.0% to 8.5%), Aboriginals (5.4% to 7.4%), and Canadians overall (4.1% to 6.4%). Conclusions: All Canadians, regardless of risk, experienced and will continue to experience a rise in diabetes. Future diabetes research involving the impact of race, culture, and ethnicity in Canadian immigrants should be holistically explored.